Comparative Study of Beef Consumers’ Preferences: Empirical Study from Traditional and Modern Markets - Rakhman, Della Puspita Putri; Mayulu, Hamdi; Fanani, Anhar Faisal; Indana, Khoiru (Faculty of Animal Science, Universitas Brawijaya, 2025)
Consumers’ preferences for beef are influenced by the interplay of intrinsic and extrinsic attributes, which affect their purchasing decisions and willingness to pay. Therefore, this study aimed to identify the key attributes influencing consumers’ purchasing power for beef in both traditional and modern markets in Samarinda City. The research was conducted in various markets in Samarinda City, East Kalimantan Province, including traditional markets (Segiri, Ijabah, Kedondong, and Rahmat) and modern markets (Hypermart Bigmall, Farmers Market Mall SCP, Foodmart Mall Lembuswana, and Lotte Grosir), using a questionnaire-based interview method. A total of 80 respondents, comprising 51 women and 29 men, were selected through purposive sampling. Primary data were collected through interviews and questionnaire responses. These were analyzed using chi-square tests and descriptive methods to assess consumers’ preferences for beef product attributes. The results showed that consumers in both traditional and modern markets preferred dark red beef with low-fat content and classified as Group One commercial cuts. The dark red beef with low-fat content is perceived as fresher and healthier (due to the lower number of calories and higher protein levels). The chi-square analysis indicated significant differences in consumers’ preferences for beef attributes between traditional and modern markets in Samarinda City, East Kalimantan Province.